Pengaruh Net Working Capital, Operation Efficiency, Struktur Modal Terhadap Kinerja Keuangan - Artila Sayyidina Fasya; Murtanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of Net Working Capital, Operational Efficiency, and Capital Structure on financial performance in banking sector companies listed on the Indonesia Stock Exchange during the period 2021–2023. Financial performance uses Return on Assets (ROA) as the main indicator. This study uses a quantitative approach with multiple linear regression methods. Secondary data were obtained from a sample of the company's annual financial reports. The results of the study indicate that Net Working Capital has a significant positive effect on financial performance. Operational Efficiency proxied by the BOPO ratio has a significant positive effect on financial performance. Meanwhile, Capital Structure does not show a significant effect on financial performance. This finding provides the essence that the efficiency of working capital and operational management is the key to increasing bank profitability, while capital structure needs to be further studied in the context of risk management.